2013
DOI: 10.1371/journal.pgen.1003855
|View full text |Cite
|
Sign up to set email alerts
|

Limiting of the Innate Immune Response by SF3A-Dependent Control of MyD88 Alternative mRNA Splicing

Abstract: Controlling infectious disease without inducing unwanted inflammatory disease requires proper regulation of the innate immune response. Thus, innate immunity needs to be activated when needed during an infection, but must be limited to prevent damage. To accomplish this, negative regulators of innate immunity limit the response. Here we investigate one such negative regulator encoded by an alternative splice form of MyD88. MyD88 mRNA exists in two alternative splice forms: MyD88L, a long form that encodes a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 86 publications
8
109
0
1
Order By: Relevance
“…In our RNA sequencing data, exon skipping accounted for 39.13% of the total alternative splicing events in HDPCs. A previous study reported that the alternative splicing of MyD88 affects the inflammatory response 23. The splicing analysis herein revealed that MyD88 produced two isoforms, namely MyD88L and MyD88S, and that the expression of MyD88S, which lacks the second exon, was significantly increased by 1.3‐fold in the siMETTL3 group compared with that in the control group in LPS‐treated HDPCs (Table 2).…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…In our RNA sequencing data, exon skipping accounted for 39.13% of the total alternative splicing events in HDPCs. A previous study reported that the alternative splicing of MyD88 affects the inflammatory response 23. The splicing analysis herein revealed that MyD88 produced two isoforms, namely MyD88L and MyD88S, and that the expression of MyD88S, which lacks the second exon, was significantly increased by 1.3‐fold in the siMETTL3 group compared with that in the control group in LPS‐treated HDPCs (Table 2).…”
Section: Resultssupporting
confidence: 51%
“…For the MyD88S‐specific primers, we used a reverse primer that spanned exons 3 to 1 and a forward primer that annealed to exon 1. For the primers that amplify both MyD88L and MyD88S, we used primers that annealed to exons 1 and 3 23. Using two sets of primers, we found that METTL3 inhibition did not significantly alter MyD88L mRNA levels but did significantly increase MyD88S mRNA levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several negative regulatory pathways have been reported, including proteins that bind an inactivate TLR signaling (1924); microRNAs that regulate expression of TLR signaling genes (25); and of innate immune genes such as IRAK2, TLR4 and MyD88 that inhibit TLR signaling Another method of down regulating TLR4 signaling is to produce an inhibitory isoform by alternatively splicing specific genes encoding essential signaling components such as IRAK2, TLR3, MD2, and MyD88 (2630). For instance, an alternatively spliced short form of MyD88 acts as a negative regulator of IL-1R/TLR/MyD88-triggered signals, leading to transcriptionally controlled negative regulation of innate immune responses (31, 32). …”
Section: Introductionmentioning
confidence: 99%